IMPLEMENTASI PENDEKATAN DEEP LEARNING TERHADAP PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Nurul Mutmainnah; Adrias Adrias; Aissy Putri Zulkarnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Deep learning is defined as an approach that emphasizes conceptual understanding and critical application of knowledge. The research aims to provide both theoretical and functional assistance in developing deep learning approaches that fit the context of elementary schools especially in mathematics learning. The methods used are qualitative with an engineering triangulation approach, including observations and interviews. The study subjects consisted of teachers and students in elementary schools. The collected data is analyzed through data reduction, data presentation, and conclusions. The results of the study show that the application of Deep Learning to mathematical studies has a positive effect on students' understanding. This method encourages students' active involvement through various interactive activities, such as simulations and experiments, making the learning process more meaningful and enjoyable. However, the application of this method is also faced with a number of challenges, such as limited time to complete the curriculum and uneven access to technology among students.